Kajian Ekspansi Akasia di Taman Wisata Alam Bukit Tangkiling - Siti Maimunah (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The aim of the research is to know the values of acacia expansion in Taman Wisata Alam Bukit Tangkiling at 500 ha at Bukit Batu district of Palangka Raya The conditions of Taman Wisata Alam Bukit Tangkiling have done reforestasi but this area hsve a specific vegetation there are acacia domination. Acacia